Patulina em maçãs armazenadas em atmosfera controlada dinâmica utilizando UPLC-MS/MS e monitoramento em supermercados - Santos, Ingrid Duarte dos (2017)
The goal of this study was to evaluate the patulin contamination in post-harvest apples submitted to different storage conditions under controlled atmosphere (CA), in addition to apples and juices available in supermarkets. In relation to apples submitted to storage, two independent experiments were performed. The first experiment was conducted in a completely randomized 2x3 factorial, totaling six treatments with four replications. Factor A was presence and absence of 1-MCP. The factor B was: i) CA with 1.2 kPa O2 and 2.0 kPa CO2; ii) DCA with chlorophyll fluorescence measurement (ACD-FC); and iii) DCA with respiratory quotient monitoring (ACD-QR 1,3). The second experiment was also conducted in a completely randomized design, totaling three treatments with four replicates. The conditions were: i) CA with 1.2 kPa O2 and 2.0 kPa CO2; ii) DCA-CF; and iii) DCA-RQ 1.3. In both experiments were used fruits from commercial orchards of the Vacaria - RS city, being stored for nine months in the mentioned conditions plus seven days of exposure at 20 °C to simulate the shelf life. Afterwards, the fruits were submitted to the analysis: decay incidence, percentage of healthy fruits and patulin occurrence. In addition, contamination with patulin was evaluated in apples and juices commercially available in supermarkets in all regions of the Santa Maria - RS city. Analytical method for patulin determination in apples and apple juice was developed and validated in CEPARC. In this method, samples were extracted with acidified ethyl acetate followed by the addition of Na 2SO4. The cleanup step uses silica and Na2 SO4). The solvent was evaporated at 65 °C and residue dissolved in acetonitrile: water (75:25). The analytical technique employed was UPLC-MS/MS. The results showed that the studied conditions of CA and DCA were not efficient to prevent the production of patulin, in both the 'Galaxy' and 'Fuji Kiku' apples, under the conditions studied in addition to 7 days exposure at 20 ºC. Healthy fruits were not contaminated with patulin present in fruits with rot. For apples 'Galaxy', the application of 1-MCP increased the percentage of fruits with rot and the patulin concentration, being not advantageous its application in this cultivar. In the 'Fuji Kiku' apples there was no significant difference between CA and DCA-CF and DCA-RQ 1.3 in the patulin concentration, although all the fruits of this cultivar showed patulin contamination even though values lower than the LMT of 50 μg kg-1. The apple and apple juice samples monitoring collected in supermarkets evidenced the presence of patulin in both matrices, with concentrations ranging from <LOQ (25 μg kg-1) to 754.4 μg kg-1, showed samples with concentrations well above the limit established by Brazilian legislation. Future studies are needed to increase the apple conservation potential, related to the new techniques of DCA (CF and RQ) and 1-MCP application in the rot determination and patulin contamination, because due to the high perishability of this fruit, control of maturation is fundamental to the increase in the shelf life postharvest, aiming at the internal market and export. In addition, the data obtained in the monitoring serve as indicative, requiring the continuation in different agricultural years.